The Comparison of Agricultural Knowledge and Information Systems (Akis) For Adopters and Non-Adopters of Good Agricultural Practices in Bafra District of Samsun, Turkey - Mustafe Abdulkadir Abdurahman; Kürşat Demiryürek; Nur İlkay Abacı (Turkish Journal of Agriculture: Food Science and Technology)
The purpose of the study is to compare Agricultural Knowledge and Information Systems (AKIS) for adopters and non-adopters of Good Agricultural Practices (GAPs) in the Bafra district of Samsun, Turkey. The main materials of this study are the data obtained from a survey and interview with adopters and non-adopters of GAPs in Bafra district. The research data were collected from 77 farmers contained both adopters and non-adopters of GAPs. Statistical analysis, such as Chi-square and t-test was used. The study results presented the socio-economic characteristics of farmers. There was a significant difference between adopters and non-adopters of GAPs, according to household size, organizational membership, farm size, livestock and crop production. Meanwhile, the information sources such as a district agricultural manager/personnel, adviser of the farmers’ union association (GAPs) and pesticide/fertilizer dealers were preferred the main sources of agricultural information for adopters of GAPs. However, it recommended that information sources like research institute, university and cooperatives needs to be improved by strengthening their way of information dissemination. In terms of usefulness of AKIS for this study, it seems that this system was insufficient to analyze this study. Even though the functions of this system are essent ial elements, they are insufficient for establishing a network of complex innovation-oriented institutional arrangements. In the future, this study suggests to analyze GAPs it needs to use Agricultural Knowledge and Innovation System (AKIS) approach, because this system have many interaction networks that can facilitate the researchers to reach the innovation easily to the intended farmers.